2012
DOI: 10.1055/s-0032-1323738
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Weight, Glucose Homeostasis, Lipid Profiles, and Metabolic Syndrome after Restrictive Bariatric Surgery

Abstract: This is the first study evaluating sleeve-gastrectomy in German patients. Our data indicate that sleeve-gastrectomy induces a similar metabolic improvement as malabsorptive surgery. Although metabolic improvement did not correlate with weight reduction, improvement almost exclusively occurred within the first 6 months, when significant weight reduction occurred. It is unclear whether this relates to the operative techniques or to the selection of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 17 publications
3
16
0
5
Order By: Relevance
“…Furthermore, after surgery, there was a reduction in plasma leptin levels and, at the sixth month, in plasma insulin and insulin resistance. This suggests that the sympathoinhibition may play a role in the favorable cardiovascular and metabolic effects of this therapeutic procedure reported in previous studies [5][6][7]10 and largely confirmed in the present one. This is not unexpected because the importance of sympathetic hyperactivity in the pathogenesis of hypertension is well documented [32][33][34] and so is, both in experimental animals and in man, its stimulating influence on leptin and insulin secretion, [35][36][37] as well as its ability to cause or worsen insulin resistance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, after surgery, there was a reduction in plasma leptin levels and, at the sixth month, in plasma insulin and insulin resistance. This suggests that the sympathoinhibition may play a role in the favorable cardiovascular and metabolic effects of this therapeutic procedure reported in previous studies [5][6][7]10 and largely confirmed in the present one. This is not unexpected because the importance of sympathetic hyperactivity in the pathogenesis of hypertension is well documented [32][33][34] and so is, both in experimental animals and in man, its stimulating influence on leptin and insulin secretion, [35][36][37] as well as its ability to cause or worsen insulin resistance.…”
Section: Discussionsupporting
confidence: 91%
“…[2][3][4] It is a widespread belief that the protective effect of bariatric surgery in obese patients may perhaps be related to a reduction of body weight per se but that the concomitant improvement of the array of risk factors commonly associated with obesity, for example, alterations in lipid and glucose metabolism, is likely to play a major role. [5][6][7] In this context, however, little attention has to date been given to whether bariatric surgery is also associated with the improvement of another adverse phenomenon of obesity (ie, sympathetic activation). 8,9 The only information available comes from 3 studies that assessed sympathetic tone by making use of spectral analysis of heart rate signal or 24-hour norepinephrine urinary excretion [10][11][12] (ie, approaches that display major intrinsic limitations not allowing to provide any direct insight on the effects of the intervention on central sympathetic outflow, as the microneurographic technique only allows to achieve 13 .)…”
mentioning
confidence: 99%
“…While studies of restrictive procedures have demonstrated correlations of triglyceride change with reductions in body weight, adiposity or insulin resistance, 17-19 the associations are much weaker in hybrid procedures. 20-23 The impacts on incretin hormones, in particular the exaggerated post-prandial GLP-1 response characteristic of RYGBP and BPD, yield improvements in insulin sensitivity beyond those expected due to weight loss alone, and beyond that seen with restrictive procedures. 24 Improved insulin sensitivity results in lower VLDL levels and, in turn, triglycerides, in patients undergoing RYGBP and BPD.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in keeping with the results of several studies and meta-analysis showing an improvement of dyslipidemia, mainly a decrease in fasting plasma triglyceride, plasma TC, and an increase in HDL-C, in the shortterm (6-12 months) or long-term (≥12 months) after bariatric surgery. 21,23,24 A few studies have investigated the effect of bariatric surgery on postprandial lipoprotein concentrations. In patients with obesity and type 2 diabetes mellitus, the plasma concentrations of triglyceride, TC, and the incremental area under the curve of triglyceride decreased and HDL-C increased after a test meal performed 2 weeks after bariatric surgery, with a similar effect after SG and BP procedures.…”
Section: Discussionmentioning
confidence: 99%